Proceedings of the International Conference on Knowledge Discovery and Information Retrieval 2014
DOI: 10.5220/0005157104440449
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Semantic Construction for Diversity-based Image Retrieval

Abstract: In recent years, the explosive growth of multimedia databases and digital libraries reveals crucial problems in indexing and retrieving images, what led us to develop our own approach. Our proposed approach TAD consists in disambiguating web queries to build an adaptive semantic for diversity-based image retrieval. In fact, the TAD approach is a puzzle constituted by three main components which are the TAWQU (Thesaurus-Based Ambiguous Web Query Understanding) process, the ASC (Adaptive Semantic Construction) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 5 publications
(5 reference statements)
0
4
0
Order By: Relevance
“…Empowered by the ubiquitous access to computer devices and the Internet, an ever-growing amount of digital images has been emerged [25]. In light of this, image retrieval is considered as an active research topic that aims at retrieving relevant images to a user query from a large database of digital images [11,14,21,26]. Until recently, most of the popular search engines (e.g., Flickr) are built upon the textual information associated with images [4,7,24].…”
Section: Introductionmentioning
confidence: 99%
“…Empowered by the ubiquitous access to computer devices and the Internet, an ever-growing amount of digital images has been emerged [25]. In light of this, image retrieval is considered as an active research topic that aims at retrieving relevant images to a user query from a large database of digital images [11,14,21,26]. Until recently, most of the popular search engines (e.g., Flickr) are built upon the textual information associated with images [4,7,24].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been extensive research on implementing thesauri in different types of digital information systems (Alonso Gaona García et al , 2014; Dalmau et al , 2005; Feki et al , 2014; Hienert et al , 2011; Lüke et al , 2012; Shiri et al , 2013). A search of the literature revealed that the majority of researchers deployed a thesaurus in real digital information systems (Alonso Gaona García et al , 2014; Dalmau et al , 2005; Feki et al , 2014; Hienert et al , 2011; Lüke et al , 2012; Shiri et al , 2013); some reported its implementation in a pilot study or in a prototype/model digital information system (Alani et al , 2000; Blocks et al , 2006; Shiri et al , 2004), and a few proposed models for its deployment in digital information systems (Maso-Maresma and Sebastia-Salat, 2013; Nakashima et al , 2003; Petrič et al , 2011). Thesauri have been used in digital information systems mainly for three purposes: indexing, searching and browsing.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, many researchers report its use in all three purposes (Atherton, 2002; Binding and Tudhope, 2004; Blocks et al , 2006; Hienert et al , 2011; Petrič et al , 2011). Furthermore, a couple of researchers used it in both indexing and searching (Shiri et al , 2011; Soo et al , 2003; Torres and Reis, 2008) and a few reported its use only in searching (Bakar and Rahman, 2003; Feki et al , 2014; Sarmento et al , 2008; Thangaraj and Gayathri, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, their performance capabilities are limited because of the semantic gap between the low level descriptors and the user understanding [7] [8] [9] . Besides, various types of social features [10][II] [12] [13](tags, locations, users, ... ) tend to effectively describe the semantic of images with the help of content features.…”
Section: Introductionmentioning
confidence: 99%